2021
DOI: 10.3389/fimmu.2021.657144
|View full text |Cite
|
Sign up to set email alerts
|

Is It Feasible to Use CMV-Specific T-Cell Adoptive Transfer as Treatment Against Infection in SOT Recipients?

Abstract: During the last decade, many studies have demonstrated the role of CMV specific T-cell immune response on controlling CMV replication and dissemination. In fact, it is well established that transplanted patients lacking CMV-specific T-cell immunity have an increased occurrence of CMV replication episodes and CMV-related complications. In this context, the use of adoptive transfer of CMV-specific T-cells has been widely investigated and applied to Hematopoietic Stem Cell Transplant patients and may be useful as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…Many clinical trials showed that ACT with EBV-specific CTLs prevented and treated PTLDs in patients with hematopoietic stem cell transplantation ( 98 102 ). EBV-specific CTLs also effectively treated PTLDs in patients with solid organ transplants that were on high immunosuppression regimens ( 93 95 , 103 , 104 ). These results have broadened the application of ACT in EBV-associated cancers, and both EBNA1 and LMP1 were the targets for the amplification of EBV-specific CTLs in the majority of studies ( 65 , 105 111 ).…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Many clinical trials showed that ACT with EBV-specific CTLs prevented and treated PTLDs in patients with hematopoietic stem cell transplantation ( 98 102 ). EBV-specific CTLs also effectively treated PTLDs in patients with solid organ transplants that were on high immunosuppression regimens ( 93 95 , 103 , 104 ). These results have broadened the application of ACT in EBV-associated cancers, and both EBNA1 and LMP1 were the targets for the amplification of EBV-specific CTLs in the majority of studies ( 65 , 105 111 ).…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…An alternative treatment approach for HCMV disease, besides anti-viral drugs, is the adoptive transfer of CD8+ Tcells (Mui et al, 2010;Garcia-Rios et al, 2021). Renzaho et al demonstrate that CD8+ T-cells not only prevent lethal MCMV disease by limiting viral spread in vital organs, but also control infection of stromal cells in the bone marrow.…”
Section: Targeting CMV Pathogenesis By Anti-viral Therapymentioning
confidence: 99%
“…An alternative treatment approach for HCMV disease, besides anti-viral drugs, is the adoptive transfer of CD8+ T-cells ( Mui et al., 2010 ; Garcia-Rios et al., 2021 ). Renzaho et al.…”
Section: Targeting CMV Pathogenesis By Anti-viral Therapymentioning
confidence: 99%
“…We hypothesize that lymphocytes from convalescent patients may contain SARS-CoV-2-specific T-cells, which can be purified and used for adoptive therapy using a cell production method developed to purify virus-specific cells. Among the methods used, the CliniMACS Prodigy system facilitates the culture and purification of primary cells, such as CAR-T-cells, previously used to treat hematological malignancies [24,25], or regulatory T-cells to attenuate graft-versus-host disease [26]. Furthermore, the CliniMACS Prodigy system has been widely used to generate specific T-cells upon stimulation with viral antigens from CMV or the Epstein-Barr virus [25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods used, the CliniMACS Prodigy system facilitates the culture and purification of primary cells, such as CAR-T-cells, previously used to treat hematological malignancies [24,25], or regulatory T-cells to attenuate graft-versus-host disease [26]. Furthermore, the CliniMACS Prodigy system has been widely used to generate specific T-cells upon stimulation with viral antigens from CMV or the Epstein-Barr virus [25,[27][28][29]. In addition, in the last decade, few studies have evidenced the stimulation of antigen-specific T-cells upon stimulation with viral-specific peptides [30,31].…”
Section: Introductionmentioning
confidence: 99%